If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 + 2x + -6 + 3x + -2 * 5x + 1 + -4x * 3 + -5 + 6 = 1 Multiply -2 * 5 5x + -3 + 2x + -6 + 3x + -10x + 1 + -4x * 3 + -5 + 6 = 1 Reorder the terms for easier multiplication: 5x + -3 + 2x + -6 + 3x + -10x + 1 + -4 * 3x + -5 + 6 = 1 Multiply -4 * 3 5x + -3 + 2x + -6 + 3x + -10x + 1 + -12x + -5 + 6 = 1 Reorder the terms: -3 + -6 + 1 + -5 + 6 + 5x + 2x + 3x + -10x + -12x = 1 Combine like terms: -3 + -6 = -9 -9 + 1 + -5 + 6 + 5x + 2x + 3x + -10x + -12x = 1 Combine like terms: -9 + 1 = -8 -8 + -5 + 6 + 5x + 2x + 3x + -10x + -12x = 1 Combine like terms: -8 + -5 = -13 -13 + 6 + 5x + 2x + 3x + -10x + -12x = 1 Combine like terms: -13 + 6 = -7 -7 + 5x + 2x + 3x + -10x + -12x = 1 Combine like terms: 5x + 2x = 7x -7 + 7x + 3x + -10x + -12x = 1 Combine like terms: 7x + 3x = 10x -7 + 10x + -10x + -12x = 1 Combine like terms: 10x + -10x = 0 -7 + 0 + -12x = 1 -7 + -12x = 1 Solving -7 + -12x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -12x = 1 + 7 Combine like terms: -7 + 7 = 0 0 + -12x = 1 + 7 -12x = 1 + 7 Combine like terms: 1 + 7 = 8 -12x = 8 Divide each side by '-12'. x = -0.6666666667 Simplifying x = -0.6666666667
| 5/8(a-2)=10 | | 6x+7=82-13 | | 36+-10=8q | | 2-2(4x+3)=18-3x+3 | | 6-a=6(1+8a) | | 30=(3w-1)xw | | 6x-4*3+7x*2-5+2-6x*3=8x | | 8x-10x=12 | | 8*3=2*2+2x-2+2-67x+2 | | 4-2(-2)=5-(-2)+1 | | (-4i)(-8-8i)(1-8i)= | | x-4=5x-8 | | 10-3x=52 | | 4x-2=8x+5-2+2-6x*3-6+2-5x+7 | | 4+5+6+7+8+9+10+11+12+13+14+15+16+17+18+19+20+21+22+23+244+5+6+7+8+9+10+11+12+13+14+15+16+17+18+19+20+21+22+23+244+5+6+7+8+9+10+11+12+13+14+15+16+17+18+19+20+21+22+23+244+5+6+7+8+9+10+11+12+13+14+15+16+17+18+19+20+21+22+23+244+5+6+7+8+9+10+11+12+13+14+15+1 | | 4(8g-1)=19+32g | | 2P=20-2(8+P) | | X10/d-3 | | 9x-28=2x+28 | | 2(x+2)=2(3x+6) | | 7x+18=x+6(4+x) | | 8*3*2-5-2x-3+4x*2*2-6=3 | | 12x+7y=15.50 | | x=x+6-2x | | 4x=5-2x+3-8+7x-4x*3-6 | | 3x(3)+1=10 | | 2x^2=51.85 | | m/17=9 | | 3y=3-x | | (3x+10)(3x+10)= | | x/-5-1=1 | | (12x^2(x^-3)^-4)/6x^5 |